The Relationship between Social Support and Academic Stress to the Onset of Suicidal Ideation in Adolescents - Dewi, Putu Diah Wilya; Sulistiowati, Ni Made Dian; Sawitri, Ni Komang Ari; Karin, Putu Ayu Emmy Savitri (Babali Publisher, 2024)
Introduction: Psychological changes like emotional disorders often occur in adolescents that can cause pressure and stress when they cannot cope well. One way to reduce the psychological pain is to self-harm to suicidal thoughts. This study aims to explore the relationship of social support and academic stress to the onset of suicidal ideation in adolescents. Method: This research used a quantitative with cross-sectional design. The respondents were 219 high school teenagers aged more than or equal to 17 years who were selected using purposive sampling techniques. This research was conducted in a senior high school in Denpasar Bali from January to May 2023. Data collection used the MSPSS questionnaire to measure social support, the ESSA questionnaire to measure academic stress, and the SIS questionnaire to measure suicidal ideation. Data were analyzed using the Spearman's rank test because the data was not normally distributed (α≤0.05). Result: The results of this study indicate that there was a significant relationship between social support (family, friends, and special people) and suicidal ideation (p=0.002; p=0.000; p=0.000); however, in the academic stress variable, it was found that there was no significant relationship with suicidal ideation in adolescents (p=0.085). Conclusion: These findings emphasize the importance of social support as a protective factor in adolescents in reducing suicidal ideation. Nursing education can be provided to teachers and students in an effort to prevent early mental health problems.